Factors affecting acceptance and use of Moodle - Šumak, Boštjan (Informatica (Ljubljana), 2011)
Advancements in web technologies and the increased influence of the World WideWeb are leading to new and innovative ways of learning. New e-learning system technologies and services enable activities that allow users to be active learners, actively participating in the on-line learning process. When an elearning system with new technologies and services is presented, it needs to be adopted by its users. The acceptance and use of an e-learning system canbe influenced by different factors. The objective of this research is to examine the factors that have an impact on studentsć perceptions about the useand acceptance of Moodle - an open source e-learning system. In this study, the technology acceptance model (TAM) was used as an underlying theory. The data, collected from 235 students, was used to test the hypothesized research model. A data analysis was performed using structural equation modelling (SEM). The results of the analysis have revealed that the actual use of Moodle depends on two main factors: behavioural intentions and attitudes toward using Moodle. Perceived usefulness was found as the strongest and the most important predictor of attitudes toward using Moodle. Several practical and theoretical implications of the present study are discussed at the end of the paper.
Keywords: spletne tehnologije; web technologies; e-učenje; semantic web; semantični splet; World Wide Web